MENGAPA DJP KALAH DALAM SENGKETA PAJAK? STUDI KASUS PADA PERUSAHAAN AIR MINUM DALAM KEMASAN - Saragi, Daniel Edgar Hirasma (JURNAL PAJAK INDONESIA, 2024)
This research is driven by the increasing trend of tax disputes in recent years, the high number of losses of the Directorate General of Taxes (DGT), and intragroup service transactions that are mostly used in tax avoidance. This research was conducted by analyzing judicial verdicts on disputes between the DGT and PT Tirta Investama due to affiliated transactions of management services. This research aims to determine the dispute resolution process and the cause of DGT's loss. The method used is qualitative, by implementing a case study. This research explains that there are . This research implies that DGT needs to evaluate and enhance the performance of the tax auditor. Suggestions of this research is DGT needs to improve several regulations related to intragroup services and burden of proof in the tax trial process.